PEMUCATAN MINYAK DAUN CENGKEH DENGAN METODE KHELASI MENGGUNAKAN ASAM SITRAT - Tri Marwati, Meika Syahbanna Rusli dan Edy Mulyono (Department of Agroindustrial Technology, Bogor Agricultural University, 2007)
ABSTRACTClove leaf oil is an essential oil that is produced by distillation of the whole leaves of clove tree. The problem which is occurred from that process was that the color of the oil is black brownish and dirty. That problem could be solved by chelating process using citric acid. Therefore, the objective of this research was to learn the mechanism of chelating process of clove leaf oil using citric acid. The mechanism of chelating process was studied by interpretation data from FTIR spectrum of clove leaf oil before and after chelating process, which is compared with FTIR spectrum of eugenol and FTIR spectrum of -cariophylen. Further study was done by learning the change of metal content, transmission and color of oil before and after chelating process. Results showed that the mechanism of chelating process : the appropriate use of citric acid permits separation of metal ions from the eugenol in the clove leaf oil and further made a complex citric acid-metal. The color of clove leaf oil changed from black brownness to yellow caused by decreasing metal content (Fe, Mg, Mn, Zn, Pb) in the oil Key word : clove leaf oil, chelating process, citric acid